2017
DOI: 10.1016/j.jiph.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Validation and adaptation of the hospital consumer assessment of healthcare providers and systems in Arabic context: Evidence from Saudi Arabia

Abstract: One of the main purposes of healthcare organizations is to serve patients by providing safe and high-quality patient-centered care. Patients are considered the most appropriate source to assess the quality level of healthcare services. The objectives of this paper were to describe the translation and adaptation process of the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey for Arabic speaking populations, examine the degree of equivalence between the original English version an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…The HCAHPS-Malay version’s Cronbach’s alpha for patient experience factors ranged between 0.69 and 0.93, which exceeds the minimum value of 0.70 for internal consistency [29]. This is consistent with reliability values from previous studies on translation of HCAHPS into non-English languages, including Dutch, French, German, Greek, Italian, and Spanish [13,15]. The study by Kemp et al [10] also showed a high Cronbach’s alpha of 0.90 overall and a range from 0.70 to 0.96 for individual domains, which indicated that the items were correlated under their domain.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The HCAHPS-Malay version’s Cronbach’s alpha for patient experience factors ranged between 0.69 and 0.93, which exceeds the minimum value of 0.70 for internal consistency [29]. This is consistent with reliability values from previous studies on translation of HCAHPS into non-English languages, including Dutch, French, German, Greek, Italian, and Spanish [13,15]. The study by Kemp et al [10] also showed a high Cronbach’s alpha of 0.90 overall and a range from 0.70 to 0.96 for individual domains, which indicated that the items were correlated under their domain.…”
Section: Discussionsupporting
confidence: 83%
“…The HCAHPS questionnaire has been translated into many languages in order to be used in other countries, so that comparisons of health services quality can be made. Studies from other countries have found that the HCAHPS is relevant for patient care experiences assessment in these countries [13,15]. This study aimed to translate and validate the HCAHPS into the Malay language and is the first report of the translation and validation of the HCAHPS questionnaire in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,17,18] Previous studies suggested that the HCAHPS® questionnaire can be used to assess patient care experiences in other countries. [12,19,20] This study aims to translate the HCAHPS® into Japanese and evaluate its validity and reliability. The translated HCHAPS® can be a useful resource for advocating patient-centred health care policy in Japan, as it allows the patient's views to be heard directly.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabic version of the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) scale measured the quality of provided care as perceived by the patients after implementing the integrated care model 24 . The HCAHPS is a standardized instrument and has been in use since 2006 to measure patients' perspectives of hospital care.…”
mentioning
confidence: 99%